THE STRATEGY OF FORMATION OF THE CONTENT OF TEACHING A FOREIGN LANGUAGE AS A REFLECTION OF SOCIO-CULTURAL DETERMINANTS OF MODERN SOCIETY - Telman Garikovich Grigoryan (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the problem of strategy of building up content of teaching a foreign language in the modern society. This includes the study of such aspects of the problem as allocation of the main algorithm of realization of strategy. Under cosideration are the main components of content of teaching and the competences developed on their basis in the Russian system. In this regard, the article examines the European competencies and attempts to analyze the structural and content parameters of the competence-based paradigm of teaching in the Russian and European systems. As a result of the analysis, it is concluded that the system of all-European competencies is presented more comprehensively breaking down into subcompetencies, while in the Russian system competences are independent components, including the communicative one. This position has been put forward by the Common European Framework system in response to the demand for multilinguism and prior communicative skills for language learners. In this connection, the question is posed that in the Russian system of competences structurally priority should be given to the communicative component as an umbellate basis for the formation of a language personality.